Ammonia Volatilization in Cocoa Farm as Affected by Sugarcane Filter Cake Supply at Different Urea and Soil Moisture Levels - Erwin Prastowo; Nadya Faiqotul Hikmah; John Bako Baon (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Ammonia  (NH3)  volatilization  is  a  crucial  mechanism  in  soil  nitrogen  (N) cycle. It accounts for main loss  of N in cocoa  farms  when  environment is  suitable to  promote  the  emission.  A  research  to  locate  a  link  of  several  factors,  namely, sugarcane filter cake  (SFC), urea  and soil moisture content  to NH 3 volatilization,  and  to reveal  cocoa  N  uptake  and  urea  fertilizer  efficiency  was  taken  place  both  in  a laboratory  with  the  incubation  technique,  and  in  a  greenhouse  as  a  pot  trial. The design was completely randomized design in factorial. The soil was Inceptisol from Kaliwining Experimental Station, Jember, East Java, collected from top soil of  a  productive  cocoa  farm.  A  closed  trap  system  was  designed  to  measurevolatilized  NH 3 from  soil  and  SFC  mixture  incubated  for  14  days.  For  the  pot experiment,  cocoa  clone  of  Scavina  6  seedlings  were  grown  for  six  months  withtreatments  involving  series  level  of  SFC  and  series  level  of  urea.  Soil  moisture content influenced volatilized NH3 by reducing 50% emission in where it was more obvious in higher level of urea applied. It was more than 90% in average for the increase in volatilized NH 3roduced by increasing in level of urea from 0 to 0.4 g kg -1 in  overall  level  of  combinations. An increase in urea  level  had  resulted in increase in  soil  pH, and  Parson correlation suggested a direct  link  with  volatilized  NH 3  We found  a  relationship  between  SFC  and volatilized  NH 3 and  their combinations  with soil  moisture  and  urea  content  were  able  to  inhibit  the  emission.  Emission decrease  up  to  28%  was  observed  from  0  to  100  g  SFC  kg-1.  This  inhibition may  have contributed to  the increase in  N cocoa  plant uptake  by  more  than  70% compared  to  control  and  subsequent  increase  in  N  fertilizer  supply  efficiency up to 86%  in the combination with 0.2  g urea  kg-1.  The absence of SFC had made a decline in urea efficiency about 20 times.Keywords: ammonia volatilization, sugarcane filter cake, urea, soil moisture, cocoa